The policy of nine-year basic education - doi: 10.4025/actascieduc.v35i2.19518 - Daniele Ramos de Oliveira; Célia Maria Guimarães (Universidade Estadual de Maringá, 2013)
A critical appraisal of the normative regulations regarding the implementation of nine-year Basic Education, published by the Brazilian Ministry of Education (MEC), between 2004 and 2010, is provided so that current changes in Basic Education in Brazil could be understood. Based on the national legal support and on arguments forwarded by several authors, current essay describes the building of a policy for the inclusion of six-year-old children in the elementary school and contextualize this historical moment in Brasil. A qualitative approach focused on documentary research showed the procedures for the location, selection and analysis of sources. Documents produced by MEC seemed to prove and convince the reader that most Brazilian states had the necessary conditions for the expansion of primary education already in 2003. Such policy may have originated within a historical moment of discourse exacerbation on childhood protection and about the establishment of educational policies that address and include all children. In fact, it was part and parcel to the worldwide movement for the education of children at an earlier age bracket.